The Development Of Classroom Reorganisation Programme For Reducing Behavioural Problems Among Severe Autism Spectrum Disorder Students In The United Arab Emirates - Al Salahat, Riyadh Abdel Rahman Salama (2024)
The United Arab Emirates is interested in improving life and training students of special needs and providing all the best programs, services, and qualified individuals to serve this category of society. Indeed, one of the most disturbing challenges for teachers of Autism Spectrum Disorder’ students is their behavioral problems and proper interaction with people in the external community. The purpose of this study was to create program’ package include two parts, designing a new physical organization for the classroom of severe autism spectrum disorder’ students, developing a training program for teachers on functional behavior assessment methods and behavior intervention plan, based on the ADDIE model. The study’ objectives aimed to evaluate the effectiveness of the old classroom organization in dealing with behavioral problems, identifying the appropriate needs and modifications for designing the new classroom organization, the level of teachers’ knowledge on functional behavior assessment methods, the effectiveness of the new classroom organization in treating students’ behavioral problems, and the efficiency of the training program to increase teachers’ knowledge on functional behavior assessment. The study’ research design is a single-group experimental study, used with the two sample groups. Implementing a classroom intervention program with 6 severe autism spectrum disorder’ students, in addition to apply a training program for 27 teachers of severe autism spectrum disorder’ students on functional behavior assessment methods.